IMPLEMENTASI STRATEGI REACT UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA PADA MATERI FLUIDA DINAMIS KELAS XI DI SMAN 7 PEKANBARU - Susanti, Dewi; ', Fakhruddin; ', Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstact: The purpose of this study is to improve student’s understanding about physic concept of fluid dynamic topic with implementation REACT strategy. There were 70 students of SMA N 7 Pekanbaru in XI MIA 2 dan XI MIA 3 participated as research subject in this study. We used lesson plan and student worksheet of fluid dynamic as learning materials. The instrument that used to measure the level of understanding physic concept was comprehension test. The data taken in this study analyzed descriptively. Based on the data analysis, we found that understanding concept of experimental class using REACT strategy better than control class using conventional learning. Thus it can be concluded that the REACT strategy can improve student’s concept understanding on fluid dynamic materials.Keywords: Fluid dynamic, REACT strategy, understanding physics concept